A comparison of levels of perfluorooctanoic acid (PFOA) and perfluorooctane sulfonic acid (PFOS) in raw and cooked fish. (2nd January 2021) - Sungur, Şana; Kanan, Erdi; Köroğlu, Muaz
Abstract: Numerous studies have been conducted to determine perfluorooctanoic acid (PFOA) and perfluorooctane sulfonic acid (PFOS) contents of fish consumed by people in different regions and countries. However, study concerning the effects of cooking on the increase or decrease of perfluorinated compounds in fish is rather limited. The effectiveness of three cooking methods (e.g. baking, boiling, frying) on reducing PFOA and PFOS levels in eight fish species was examined. All cooking methods reduced PFOA and PFOS concentrations. The results showed that the greatest reduction in fish PFOA and PFOS contents occurred in the frying of sunflower oil for 20 min. As a result of the 20 min frying process in sunflower oil, 70% to 86% decrease in PFOA amounts and 82% to 89% reduction in PFOS amounts were determined.